2021
DOI: 10.3390/geosciences11110478
|View full text |Cite
|
Sign up to set email alerts
|

Volcanic Gas Hazard Assessment in the Baia di Levante Area (Vulcano Island, Italy) Inferred by Geochemical Investigation of Passive Fluid Degassing

Abstract: In a volcanic area, the composition of air is influenced by the interaction between fluids generated from many different environments (magmatic, hydrothermal, meteoric, and marine). Any physical and chemical variation in one of these subsystems is able to modify the outgassing dynamic. The increase of natural gas hazard, related to the presence of unhealthy components in air, may depend on temporary changes both in the pressure and chemical gradients that generate transient fluxes of gases and can have many di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 55 publications
(85 reference statements)
0
12
0
Order By: Relevance
“…As far as we are aware, no other studies are found in the literature that attempt to propose risk maps for indoor environments based on soil degassing mapping. Considering the recent unrest period at Vulcano Island (Italy) (Diliberto et al, 2021;Di Martino et al, 2022) as well as the anomalous CO 2 degassing detected in La Bombilla and Puerto Naos (La Palma, Spain) after the 2021 volcanic eruption, the application of these methodologies to define susceptibility and risk maps may be helpful tools to be used by authorities and land-use planners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as we are aware, no other studies are found in the literature that attempt to propose risk maps for indoor environments based on soil degassing mapping. Considering the recent unrest period at Vulcano Island (Italy) (Diliberto et al, 2021;Di Martino et al, 2022) as well as the anomalous CO 2 degassing detected in La Bombilla and Puerto Naos (La Palma, Spain) after the 2021 volcanic eruption, the application of these methodologies to define susceptibility and risk maps may be helpful tools to be used by authorities and land-use planners.…”
Section: Discussionmentioning
confidence: 99%
“…In what concerns outdoor environments, CO 2 usually dilutes in the atmosphere, as shown by several gas dispersion models applied in diffuse degassing sites (Pareschi et al, 1999;Costa et al, 2008;Chiodini et al, 2010;Granieri et al, 2013;Massaro et al, 2021;Massaro et al, 2022;Rave-Bonilla et al, 2023;Viveiros et al, 2023). However, under certain circumstances and in confined spaces, hazardous concentrations may still be detected (Diliberto et al, 2021;Viveiros et al, 2023). Hazard maps produced based on the dispersion models do not account for indoor CO 2 exposure, where lethal concentrations may be detected (Viveiros et al, 2009;Viveiros et al, 2015;Barberi et al, 2019;Carapezza et al, 2023).…”
mentioning
confidence: 99%
“…Nowadays, the real-time multiparametric monitoring network includes thermal and visible cameras, both permanent and temporary seismic and GNSS stations, bore-hole tiltmeters and SAR interferometry and automatic single gas and multigas-type stations (Aiuppa et al, 2022;Diliberto et al, 2021;Selva et al, 2020). Finally, a GBRAR (Ground Based Real Aperture Radar) installed at the Geophysical Observatory is able to measure at high frequency the ground deformation on the northern slope of La Fossa cone.…”
Section: La Fossa Cone Entered a New Phase Of Unrest Betweenmentioning
confidence: 99%
“…The already mentioned unrest episodes, which occurred in the late 1970s, were tracked by a comprehensive geochemical and geophysical surveillance network, now run by the INGV (Istituto Nazionale di Geofisica e Vulcanologia), implemented on the island since 1981. Currently, La Fossa cone is characterized by low‐level seismicity and intense hydrothermal activity, small ground deformations and rapid changes in the geomorphology due to the now frequent heavy rains, which are deepening the cuttings on flanks and also eroding the mainly loose deposits that cover the rims and slopes of the edifice (Aiuppa et al, 2022; Bonadonna et al, 2022; Diliberto et al, 2021; Selva et al, 2020). Going into details related to the last decades:…”
Section: Non‐eruptive Periodsmentioning
confidence: 99%
See 1 more Smart Citation